Targeting tumor micro-environment for design and development of novel anti-angiogenic agents arresting tumor growth - Gacche, Rajesh N.; Meshram, Rohan J. (Progress in biophysics and molecular biology, 2013)
Angiogenesis: a process of generation of new blood vessels has been proved to be necessary for sustained tumor growth and cancer progression. Inhibiting angiogenesis pathway has long been remained a significant hope for the development of novel, effective and target orientated antitumor agents arresting the tumor proliferation and metastasis. The process of neoangiogenesis as a biological process is regulated by several pro- and anti-angiogenic factors, especially vascular endothelial growth factor, fibroblast growth factor, epidermal growth factor, hypoxia inducible factor 1 and transforming growth factor. Every endothelial cell destined for vessel formation is equipped with receptors for these angiogenic peptides. Moreover, numerous other angiogenic cytokines such as platelet derived growth factor (PGDF), placenta growth factor (PGF), nerve growth factor (NGF), stem-cell factor (SCF), and interleukins-2, 4, 6 etc. These molecular players performs critical role in regulating the angiogenic switch. Couple of decade's research in molecular aspects of tumor biology has unraveled numerous structural and functional mysteries of these angiogenic peptides. In present article, a detailed update on the functional and structural peculiarities of the various angiogenic peptides is described focusing on structural opportunities made available that has potential to be used to modulate function of these angiogenic peptides in developing therapeutic agents targeting neoplastic angiogenesis. The data may be useful in the mainstream of developing novel anticancer agents targeting tumor angiogenesis. We also discuss major therapeutic agents that are currently used in angiogenesis associated therapies as well as those are subject of active research or are in clinical trials.